1982
DOI: 10.1007/bf00442336
|View full text |Cite
|
Sign up to set email alerts
|

A case of Down's syndrome resulting from mirror duplication of chromosome 21

Abstract: Abstract. Cytogenetic analysis of a 1-month-old boy with a phenotype similar to that typical for Down's syndrome revealed 46 chromosomes with a mirror duplication of chromosome 21. SOD-1 concentration was increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In 1965, Lejeune et al 1965 suggested a tandem inverse duplication in these patients. Subsequently, a few cases have been published [Turleau et al, 1980; Pfeiffer and Loidl, 1982; Stoll et al, 1982; Pangalos et al, 1992b; Gutierrez‐Angulo et al, 1999; Barbi et al, 2000; Cortes‐Gutierrez et al, 2002; Wandall et al, 2002; Sheth et al, 2007; Egashira et al, 2008]. In this study, we report on a DS child with karyotype 46,XX,idic(21)(q22.3).…”
Section: To the Editormentioning
confidence: 99%
“…In 1965, Lejeune et al 1965 suggested a tandem inverse duplication in these patients. Subsequently, a few cases have been published [Turleau et al, 1980; Pfeiffer and Loidl, 1982; Stoll et al, 1982; Pangalos et al, 1992b; Gutierrez‐Angulo et al, 1999; Barbi et al, 2000; Cortes‐Gutierrez et al, 2002; Wandall et al, 2002; Sheth et al, 2007; Egashira et al, 2008]. In this study, we report on a DS child with karyotype 46,XX,idic(21)(q22.3).…”
Section: To the Editormentioning
confidence: 99%